Speedtest and Ekahau Site Survey Application Training in West Jakarta Schools 2021 - Imelda Uli Vistalina Simanjuntak; Yosy Rahmawati; Ellisa Agustina; Ketty Siti Salamah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Kindergarten teachers have been integrating technology into their teaching routine activities in Indonesia during the Covid-19 pandemic. When it comes to kindergartners, teachers cannot do much of anything remotely, particularly if pupils must sit and gaze at a computer for hours on end. Penguin Family Islamic Preschool Teacher will be prepared to create effective and efficient technology-based in this community project. Socialization and continuity guidance was the major activities. Qualitative analysis is employed for data analysis, data reduction, data presentation, and deriving conclusions. The result of discussions’ community services is 1) find online resources before you start student teaching; 2) invite parents to participate; 3) examine each child's activities; 4) enlist every student's participation; 5) help develop fine motor abilities; 6) learn about developmental-appropriate practice; 7) know your lesson plan; 8) educate socially; 9) observe the routine procedures. The conclusion is Kindergarteners are still learning to think critically, and they may lack group-work experience and struggle with self-discipline in an online environment. Simple procedures may require detailed instruction in the online environment.